Analysis of Sources and Use of Capital In Buku IV Bank Listed On The Indonesian Stock Exchange - Noer Huda; Alwi (Pustaka Digital Indonesia, 2023)
In today's highly competitive global banking industry, efficiency is crucial for success. One key measure of bank efficiency is its ability to generate income relative to its working capital. Working capital, which funds daily operations, includes short-term assets like cash, receivables, inventory, and current liabilities. Indonesia's banking sector, divided into four commercial activity groups (Book IV) based on core capital, is the focus of this study. Specifically, it examines Bank Rakyat Indonesia (BRI) and Bank Central Asia (BCA), two banks with the highest core capital in the Book IV category. The research aims to evaluate the effectiveness of their working capital management by analyzing their working capital turnover ratios from 2014 to 2020. The problem identified is the fluctuating working capital turnover ratios in these banks, raising concerns about their working capital management. The research question explores the effectiveness of managing sources and use of working capital in these two Book IV banks in Indonesia. The literature review provides definitions of working capital, its sources and uses, and the working capital turnover ratio. Hypotheses are formulated to test the effectiveness of working capital management in the selected banks. The research methodology involves descriptive analysis using financial reports from 2014-2020 and the one-sample T-test to compare working capital turnover ratios. The results show that BRI Bank exhibited fluctuations but demonstrated effectiveness in 2018 and 2020, while BCA Bank's ratios also fluctuated but remained less effective. In conclusion, both banks face challenges in effectively managing their working capital, primarily due to low liquidity for supporting operations. Suggestions include regular evaluations of working capital and expanding research to gain more comprehensive insights into banking sector management.